Evaluation of IL-6, FoxP3 Treg lymphocytes, intestinal barrier biomarkers and the use of synbiotics in obese adolescents: a pilot study - Aziz, Cylmara; Morales, Armando; Pinto, Walter; Fanchini, Vanessa; Dell Aquila, Luis; Sangaleti, Carine; Elias, Rosilene; Dalboni, Maria (Frontiers in Pediatrics, 2023)
Aim: This prospective pilot study evaluated inflammatory and intestinal barrier biomarkers and the effects of a synbiotic in obese adolescents. Methods: Eighteen obese and 20 eutrophic adolescents were evaluated for body composition using bioimpedance analysis (BIA), body mass index (BMI), IL-6 and lipopolysaccharide (LPS) serum levels, CD4 and FoxP3 Treg lymphocytes and monocytes. Synbiotic supplementation for 60 days was also evaluated for these parameters only in obese adolescents. Results: We observed an increase in CD4 lymphocyte (18.0 ± 12.4 vs. 8.9 ± 7.5; p<0.01), IL-6 (0.30 ± 0.06 vs. 0.20 ± 0.06; p = 0.02) and LPS (0.18 ± 0.15 vs. 0.08 ± 0.05; p<0.01) levels in obese compared to eutrophic adolescents. After synbiotic supplementation, FoxP3 Treg lymphocytes increased (14.0 ± 6.7 vs. 9.9 ± 5.4; p = 0.02) in obese adolescents. Conclusions: Obese adolescents presented a state of microinflammation and intestinal barrier breakdown, and synbiotic supplementation increased the expression of FoxP3 Treg lymphocytes, an anti-inflammatory regulator. Whether the increase in FoxP3 Treg lymphocytes may have an impact on inflammation and outcomes in obese adolescents deserves further evaluation.